2013
DOI: 10.1093/infdis/jit182
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Zoster Vaccine in Elderly Adults Following Documented Herpes Zoster

Abstract: These results demonstrate that the general safety of zoster vaccine in older persons is not altered by a recent history of documented HZ, supporting the safety aspect of the Centers for Disease Control and Prevention Advisory Committee on Immunization Practices recommendation to administer zoster vaccine to all persons ≥ 60 years of age with no contraindications, regardless of a prior history of HZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Additionally, causality cannot usually be established when the only evidence is a temporal association [35]. However, despite these limitations, this review confirmed that the overall safety profile of ZVL following post-marketing use is consistent with safety findings reported in pivotal clinical trials with the vast majority (93%) of the AE reported as non-serious and ISRs being the most common AE reported [3,4,11,36]. …”
Section: Discussion/conclusionsupporting
confidence: 70%
“…Additionally, causality cannot usually be established when the only evidence is a temporal association [35]. However, despite these limitations, this review confirmed that the overall safety profile of ZVL following post-marketing use is consistent with safety findings reported in pivotal clinical trials with the vast majority (93%) of the AE reported as non-serious and ISRs being the most common AE reported [3,4,11,36]. …”
Section: Discussion/conclusionsupporting
confidence: 70%
“…[59][60][61] It is highly recommended for the immunization of immuno-competent individuals over age 60 y with no history of recent HZ. [62][63][64] Given the current severity and high costs of HZ disease and the uncertainty of the epidemiological and economic impact of widespread childhood varicella vaccination on the incidence of zoster, it is important to establish surveillance and to monitor the population-based impact of both vaccinations. 52 In the USA, Patel et al have estimated that, while VZ vaccination has contributed to saving up to $100-150 million/year, this potential saving could be outweighed by an increase in HZ-related costs (up to $700 million/year).…”
Section: Discussionmentioning
confidence: 99%
“…33 The vaccine can be given to persons with a prior history of herpes zoster; in a recent report, rates of adverse events associated with vaccination were similar between those who had prior zoster (mean 3.6 years prior to vaccination) and those with no history of zoster. 37 …”
Section: Strategies and Evidencementioning
confidence: 99%